2022
DOI: 10.1038/s41467-022-30423-3
|View full text |Cite
|
Sign up to set email alerts
|

Earth’s geodynamic evolution constrained by 182W in Archean seawater

Abstract: Radiogenic isotope systems are important geochemical tools to unravel geodynamic processes on Earth. Applied to ancient marine chemical sediments such as banded iron formations, the short-lived 182Hf-182W isotope system can serve as key instrument to decipher Earth’s geodynamic evolution. Here we show high-precision 182W isotope data of the 2.7 Ga old banded iron formation from the Temagami Greenstone Belt, NE Canada, that reveal distinct 182W differences in alternating Si-rich (7.9 ppm enrichment) and Fe-rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Hence, they trace the source of components affecting local seawater composition (e.g., Viehmann et al, 2015). This is in marked contrast to the 182 W systematics in the Temagami BIF investigated by Mundl-Petermeier et al (2022), where positive μ 182 W anomalies were observed. While μ 182 W tracks metal-silicate partitioning and earlier differentiation events than μ 142 Nd, generally they should show similar trends.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Hence, they trace the source of components affecting local seawater composition (e.g., Viehmann et al, 2015). This is in marked contrast to the 182 W systematics in the Temagami BIF investigated by Mundl-Petermeier et al (2022), where positive μ 182 W anomalies were observed. While μ 182 W tracks metal-silicate partitioning and earlier differentiation events than μ 142 Nd, generally they should show similar trends.…”
Section: Introductionmentioning
confidence: 82%
“…The Temagami region has suffered only minor metamorphism (lower greenschist facies; Jolly, 1982) and hosts sedimentary deposits, including banded iron formations (BIF) that give internal Sm-Nd and Lu-Hf isochron ages of 2.7 Ga and for which the 143 Nd isotope compositions have been shown to derive from local Abitibi seawater (Viehmann et al, 2014). The banded iron formation at Temagami is a layered marine chemical sediment with alternating bands of Fe-rich magnetite and Si-rich metachert, showing evidence that both high temperature hydrothermal fluids and subaerial terrestrial weathering affected 2.7 Ga Temagami seawater chemistry (Bau and Alexander, 2009;Viehmann et al, 2014;Bau et al, 2022;Mundl-Petermeier et al, 2022). Previous work has shown that the Temagami BIF has unaltered rare earth element (Bau and Alexander, 2009; Supplementary Information), 143 Nd and 176 Hf isotope compositions (Viehmann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the W budget of seawater is ultimately controlled by igneous rocks (Kurzweil et al, 2021) and positive μ 182 W anomalies are dominant in global Paleoarchean rock data (e.g., Puchtel et al, 2022;Tusch et al, 2021;Willbold et al, 2011). This assumption is confirmed by the isotopic composition of banded iron formations, which show positive μ 182 W values throughout the Archean (Mundl-Petermeier et al, 2022;Tusch et al, 2021). Fluid-rock interaction involving seawater can therefore not explain the negative μ 182 W values in the volcanic rocks of the Kaapvaal Craton.…”
Section: Origin Of W-rich Fluids In the Kaapvaal Cratonmentioning
confidence: 99%
“…2012, Mundl‐Petermeier et al . 2022). Initially, radiogenic 182 W isotope measurements were conducted by negative‐thermal ionisation mass spectrometry (N‐TIMS) for the meteorite samples (Harper et al .…”
mentioning
confidence: 99%
“…The short-lived 182 Hf-182 W system acts as one of the most effective tools in deciphering the origin of the early solar system, and the formation and evolution of planets (Kleine et al 2009, Mundl-Petermeier et al 2022. Initially, radiogenic 182 W isotope measurements were conducted by negative-thermal ionisation mass spectrometry (N-TIMS) for the meteorite samples (Harper et al 1991).…”
mentioning
confidence: 99%